Sensitive quantification of dipicolinic acid from bacterial endospores in soils and sediments. (21st December 2020) - Rattray, Jayne E.; Chakraborty, Anirban; Li, Carmen; Elizondo, Gretta; John, Nisha; Wong, Michelle; Radović, Jagoš R.; Oldenburg, Thomas B. P.; Hubert, Casey R. J.
Summary: Endospore‐forming bacteria make up an important and numerically significant component of microbial communities in a range of settings including soils, industry, hospitals and marine sediments extending into the deep subsurface. Bacterial endospores are non‐reproductive structures that protect DNA and improve cell survival during periods unfavourable for bacterial growth. An important determinant of endospores withstanding extreme environmental conditions is 2, 6‐pyridine dicarboxylic acid (i.e. dipicolinic acid, or DPA), which contributes heat resistance. This study presents an improved HPLC‐fluorescence method for DPA quantification using a single 10‐min run with pre‐column Tb 3+ chelation. Relative to existing DPA quantification methods, specific improvements pertain to sensitivity, detection limit and range, as well as the development of new free DPA and spore‐specific DPA proxies. The method distinguishes DPA from intact and recently germinated spores, enabling responses to germinants in natural samples or experiments to be assessed in a new way. DPA‐based endospore quantification depends on accurate spore‐specific DPA contents, in particular, thermophilic spores are shown to have a higher DPA content, meaning that marine sediments with plentiful thermophilic spores may require spore number estimates to be revisited. This method has a wide range of potential applications for more accurately quantifying bacterial endospores in diverse environmental samples.